PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM KELOMPOK PADA MATA PELAJARAN IPA DI KELAS V SEKOLAH DASAR - Maulina, Wulan Siti (2017)
This research is motivated by the low level of active participation of students in groups that should be interdependent positive, thus impacting on the achievement of group objectives and mastery of the subject. The researcher chooses cooperative model of Group Investigation type to solve the problem. The purpose of this research is to know the learning step by applying Group Investigation, and increasing the active participation of students in the group and the result of learning after applied the model. The research is Classroom Action Research, with 2 cycles through quantitative and qualitative data analysis techniques. Through Group Investigation, students actively conduct investigations in group based on the division of tasks performed, on the subtopics that have been determined. Initial conditions indicate the percentage of students with active participation categories in the group is only 28,125%. After being given action on the first cycle the classical average of active participation of students in the group reached 66%, and in cycle II increased to 88%. Classical completeness of student learning outcomes in the first cycle is 71.875%, and increased in cycle II to 81.25%. It can be concluded that cooperative learning model of Group Investigation type is effective in increasing the active participation of the students in the group as well as the learning outcomes. Penelitian ini dilatarbelakangi oleh masih rendahnya partisipasi aktif siswa dalam kelompok yang semestinya dapat saling bergantung positif, sehingga berdampak pada pencapaian tujuan kelompok dan penguasaan materi. Peneliti memilih model kooperatif tipe Group Investigation untuk mengatasi masalah tersebut. Tujuan penelitian adalah untuk mengetahui langkah pembelajaran dengan menerapkan Group Investigation dan peningkatan partisipasi aktif siwa dalam kelompok serta hasil belajarnya setelah diterapkan model tersebut. Penelitian yang dilakukan adalah Penelitian Tindakan Kelas dengan 2 siklus, melalui teknik analisis data kuantitatif dan kualitatif. Melalui Group Investigation, siswa aktif melakukan investigasi dalam kelompok berdasarkan pembagian tugas yang dilakukan, mengenai subtopik yang telah ditentukan. Kondisi awal menunjukkan persentase siswa dengan kategori aktif berpartisipasi dalam kelompok hanya 28,125%. Setelah diberi tindakan pada siklus I rata-rata klasikal partisipasi aktif siswa dalam kelompok mencapai 66%, dan pada siklus II meningkat menjadi 88%. Ketuntasan klasikal hasil belajar siswa pada siklus I mencapai 71,875%, dan meningkat pada siklus II menjadi 81,25%. Dapat disimpulkan bahwa model pembelajaran kooperatif tipe Group Investigation efektif dalam meningkatkan partisipasi aktif siswa dalam kelompok serta hasil belajarnya. ----------